Smart fertigation system with mobile application and fuzzy logic optimization - Izahar, Nurul Anis Zulaikha; Derahman, Mohd Noor; Mohamed, Mohamad Afendee; Sitanggang, Imas Sukaesih (Accent Social and Welfare Society, 2023)
Precision farming plays a pivotal role in addressing the dual challenge of increasing crop productivity and reducing the environmental impact of agriculture. This arises from the critical need to elevate crop productivity to meet the increasing global demand for food, while actively confronting the economic and environmental consequences linked to suboptimal conventional farming practices. Conventional agriculture consistently grapples with inefficiencies in resource management, marked by the impractical and excessive utilization of fertilizers and water. This not only results in mounting production costs, but also gives rise to substantial threats to the environment, encompassing soil degradation, water pollution, and the loss of biodiversity. Thus, this study introduces a smart fertigation system, incorporating internet of things (IoT) technology and fuzzy logic optimization, specifically designed for large-scale bird's eye chili production. The innovative system integrates IoT technology with fuzzy logic to fine-tune fertilization and irrigation processes. Notably, a fuzzy inference system, implemented using MATLAB and arduino UNO, dynamically optimizes nutrient delivery according to the growth stage of the chili plants. This sophisticated approach ensures that fertilization is precisely tailored to the specific needs of the crops at each developmental phase. Additionally, the development of the C-farm mobile application empowers farmers with remote monitoring capabilities, enabling them to oversee and manage the system from anywhere. This mobile application provides real-time insights into the smart fertigation system, granting farmers unprecedented control over their agricultural operations. Our findings also highlight the efficacy of fuzzy logic in enhancing the precision of automated fertigation systems. By dynamically adjusting nutrient delivery in response to the nuanced growth stages of chili plants, our system demonstrates its adaptability and responsiveness, resulting in optimized resource utilization and improved crop outcomes. This innovative integration of technology not only holds promise for large-scale crop production but also addresses the pressing issues of water and fertilizer waste in contemporary agriculture. As we move towards a more sustainable and efficient agricultural paradigm, our smart fertigation system, with its fuzzy logic optimization and remote monitoring capabilities, stands as a beacon of progress in the quest for precision farming.